Development and Antibacterial Characterization of Hand Sanitizer Gel from Mint Leaf Extract (Mentha arvensis L.) - Malarvarnan, S.; Nirubini, A.S.; Sivasinthujah, S.; Gnanakarunyan, T.J. (: Faculty of Graduate Studies, General Sir John Kotelawala Defence University, Sri Lanka, 2024)
Formulation of hand sanitizers with herbs extract to enhance safety and quality while maintaining effective antibacterial properties. This study aimed to formulate hand sanitizers with different concentrations of ethyl acetate extracts of Mentha arvensis leaves and assess their physiochemical properties and antibacterial activities. The plant material was collected in Jaffna and allowed to shade dry. The dried plant material was macerated with ethyl acetate for 48 hrs at room temperature. Two different formulations (A and B) were prepared with 5% and 10% plant extract. Organoleptic characteristics, pH, homogeneity, turbidity, and antibacterial activity were evaluated. The antimicrobial activity of formulations was estimated using the agar well diffusion method against Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli by employing a formulation excluding plant extract as control and WHO standard hand sanitizer used as a positive control. Results indicated that Formulation B, containing 10% extract, demonstrated satisfactory physiochemical properties and antibacterial activity against the tested bacteria. Formulation A showed a maximum inhibition of 10.60 ± 0.58 mm against E. coli at 800 μg/ml, with no activity against S. aureus and P. aeruginosa at lower concentrations. In contrast, Formulation B demonstrated greater efficacy, achieving inhibition zones of 14.17 ± 1.04 mm for E. coli, 10.17 ± 1.04 mm for S. aureus, and 3.83 ± 0.76 mm for P. aeruginosa at 800 μg/ml. These results indicate that Formulation B shows significant potential as an effective hand sanitizer. Further stability evaluation of formulation B will ensure the evaluation of the clinical usage.